THRESHOLD SENSITIVE WIRELESS SENSOR NETWORK WITH IMPROVED LEACH - kajla, Raghuveer; mandal, Sandip (IJRDO -Journal of Computer Science Engineering, 2015)
The foremost difference between the WSN and the traditional wireless networks is that sensors are extremely sensitive to energy consumption. Energy saving is the crucial issue in designing the wireless sensor networks. LEACH Protocol plays an important role in response to the uneven energy distribution that is caused by the randomness of cluster heads forming .LEACH adopts a hierarchical and adaptive approach to organize the network into a set of clusters, managed by selected CHs . Further, the proposed system improves the parent network into the most prominent wireless sensor network’s routing protocol “LEACH” as TSWSN with Improved LEACH by introducing efficient cluster head replacement scheme and efficient transmitting power levels. The implementation of the clustering algorithms including the proposed advanced LEACH protocol is done using MATLAB. Keywords-Threshold value(tv), sensing value(sv), Threshold sensitive wireless sensor network(TSWSN), Base station(BS) , Clustering algorithms.